AN ANNOTATED TRANSLATION OF LOVE BEYOND REASON BY KAREN VAN DER ZEE - Wijayanti, Dyah Kartika; Said, Mashadi (Universitas Gunadarma, 2014)
This is an annotated translation research, a translation with commentary. The problems of this research are: 1) What are the difficulties encountered in the course of translation? 2) How does the researcher cope with the difficulties in order to get the solutions? This research aims to: 1) find out the difficulties coming up when translating the source text; 2) solve the difficulties that come across when translating the source text. The methods used in this research are introspective and retrospective methods. The results of this research show that there are 125 items of difficulties, namely 100 items of lexicon, 5 items of grammatical structure, 20 items of cultural context, and no communication situation found. Keywords: annotated, translation, strategies, theories.